The impact of intensive care unit physician staffing change at a community hospital - Christopher D Adams; Luigi Brunetti; Liza Davidov; Jose Mujia; Michael Rodricks (SAGE Open Medicine, 2022)
Objectives: A high-intensity staffing model has been defined as either mandatory intensivist consultation or a closed intensive care unit in which intensivists manage all aspects of patient care. In the current climate of limited healthcare resources, transitioning to a closed intensive care unit model may lead to significant improvements in patient care and resource utilization. Methods: This is a single-center, retrospective cohort study of all mechanically ventilated intensive care unit admissions in the pre-intensive care unit closure period of 1 October 2014 to 30 September 2015 as compared with the post-intensive care unit closure period of 1 November 2015 to 31 October 2016. Patient demographics as well as outcome data (duration of mechanical ventilation, length of stay, direct costs, complications, and mortality) were abstracted from the electronic health record. All data were analyzed using descriptive and inferential statistics. Regression analyses were used to adjust outcomes for potential confounders. Results: A total of 549 mechanically ventilated patients were included in our analysis: 285 patients in the pre-closure cohort and 264 patients in the post-closure cohort. After adjusting for confounders, there was no significant difference in mortality rates between the pre-closure (40.7%) and post-closure (38.6%) groups (adjusted odds ratio = 0.82; 95% confidence interval = 0.56–1.18; p = 0.283). The post-closure cohort was found to have significant reductions in duration of mechanical ventilation (3.71–1.50 days; p < 0.01), intensive care unit length of stay (5.8–2.7 days; p < 0.01), hospital length of stay (10.9–7.3 days; p < 0.01), and direct hospital costs (US $16,197–US $12,731; p = 0.009). Patient complications were also significantly reduced post-intensive care unit closure. Conclusion: Although a closed intensive care unit model in our analysis did not lead to a statistical difference in mortality, it did demonstrate multiple beneficial outcomes including reduced ventilator duration, decreased intensive care unit and hospital length of stay, fewer patient complications, and reduced direct hospital costs.